Evidence of an evolved nature of MWC 349A - Kraus, Michaela (2020)
The Galactic emission-line object MWC 349A is one of the brightest radio stars in the sky. The central object is embedded in an almost edge-on oriented Keplerian rotating thick disc that seems to drive a rotating bipolar wind. The dense disc is also the site of hot molecular emission such as the CO bands with its prominent band heads in the near-infrared spectral range. Despite numerous studies, the nature of MWC 349A is still controversial with classifications ranging from a pre-main sequence object to an evolved supergiant. We collected new high-resolution near-infrared spectra in the K- and L-bands using the GNIRS spectrograph at Gemini-North to study the molecular disc of MWC 349A, and in particular to search for other molecular species such as SiO and the isotope 13CO. The amount of 13CO, obtained from the 12CO/13CO ratio, is recognized as an excellent tool to discriminate between pre-main sequence and evolved massive stars. We find no signatures of SiO band emission, but detect CO band emission with considerably lower intensity and CO gas temperature compared to previous observations. Moreover, from detailed modelling of the emission spectrum, we derive an isotope ratio of 12CO/13CO = 4 +- 1. Based on this significant enrichment of the circumstellar environment in 13CO we conclude that MWC 349A belongs to the group of B[e] supergiants, and we discuss possible reasons for the drop in CO intensity.